How to build the permanently innovative company: five tested sets of management practices. Issue 1 (19th January 2015) - Engel, Kai; Dirlea, Voletka; Dyer, Stephen; Graff, Jochen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This article reports on the findings of the Best Innovator competition, which was launched in Germany in 2003, to identify and communicate the best practices of innovation management of the country's businesses. After ten years of research, the contest has not only been expanded to identify the most innovative companies in much of the developed world but also to document the success of their best practices over time. Design/methodology/approach – This article details five tested sets of best practices. Findings – A major research finding is the strong correlation between superior innovation management capabilities and sustainable, profitable growth. Another finding was that, given the mix of industries, the diversity of businesses and the range of sizes in the Best Innovator club, it is striking that there is no correlation between R&D budget and innovation. Practical implications – Best Innovators first develop and then manage their innovation portfolios. All of them pursue clarity on a fundamental question: what do we want our innovation strategy to do for us? Originality/value – The researchers found that to get their innovation strategies right, Best Innovators invest upfront in understanding market, technology and service dynamics. They are investing time more than money. Leaders can learn how Best Innovators address innovation management "from the market to the market" and manipulate five areas to improve their innovation performance and propel sustainable and profitable growth.